The impact of the circular economy on the development of small business - Korobka, S. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article examines the impact of the circular economy on the development of small businesses, identifies key benefits and challenges they face during the transition to a new business model. The main principles of the circular economy are described, such as reducing the use of primary resources, reusing materials, recycling waste, and creating closed production cycles. The role of small businesses in implementing circular approaches, their ability to quickly adapt to changes, and test new business models and technological solutions is analyzed. The advantages of the transition to a circular economy are outlined, including increasing the competitiveness of enterprises, creating new jobs, reducing the negative impact on the environment, and streamlining production processes. At the same time, the main challenges that hinder this process are considered, including the need for significant initial investments, technological difficulties, the need for changes in consumer habits, and insufficient awareness of businesses about circular practices. The important role of state support in creating favorable conditions for the transition of small businesses to a circular economy is identified, in particular through financial incentives, educational programs and improving the regulatory environment. Particular attention is paid to the prospects for the integration of Ukrainian enterprises into international environmental initiatives and the possibilities for developing cooperation between business, the state and public organizations to form sustainable economic models. It is concluded that the circular economy opens up wide opportunities for small businesses, contributing to more efficient use of resources, cost reduction and the introduction of innovations. However, to fully realize its potential, comprehensive measures are needed, including financial support, infrastructure development, technological innovations and changes in consumer culture.